2010
DOI: 10.1192/apt.bp.107.005082
|View full text |Cite
|
Sign up to set email alerts
|

Asperger syndrome and criminal behaviour

Abstract: SummaryThe importance of considering antisocial behaviour among people with autism-spectrum disorders is apparent from the significant number of case reports and case series describing criminal behaviour of people with a diagnosis of Asperger syndrome. The evidence so far does not support a specific association between the syndrome and criminal offending. However, a small yet significant number of offenders with autism who engage in illegal behaviour find themselves socially excluded or detained in secure prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 20 publications
2
52
0
Order By: Relevance
“…There is debate in the literature over whether offending behaviour in ASD is associated with psychopathy or not (see Dein and Woodbury-Smith, 2010). The rate of lifetime physical violence in the ASD group was high at 78 per cent but significantly lower than that found in the control group (93 per cent).…”
Section: Discussionmentioning
confidence: 99%
“…There is debate in the literature over whether offending behaviour in ASD is associated with psychopathy or not (see Dein and Woodbury-Smith, 2010). The rate of lifetime physical violence in the ASD group was high at 78 per cent but significantly lower than that found in the control group (93 per cent).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that training to increase the ability of prison staff to recognise symptoms of ASD, the development of specific pathways of care for individuals with ASD in prison and the introduction of specialist wings for prisoners with ASD may help to improve their custodial experience. In an earlier paper the same authors also highlighted the need for care when managing transitions through the CJS (Dein and Woodbury-Smith, 2010). Another paper suggested that mental health staff could improve the management of prisoners with ASD by undertaking an educational and consultative role with prison and court staff (Freckelton, 2013).…”
Section: Management Of People With Autistic Spectrum Disorders In Primentioning
confidence: 99%
“…Mouridsen et al (2008) suggested that neurocognitive problems and associated psychiatric illness are important risk factors to consider. Indeed, antisocial personality disorder has been noted amongst offenders with ASD (Dein & Woodbury"Smith, 2010;Långström, Grann, Ruchkin, Sjöstedt, & Fazel, 2009). It is possible that such difficulties remain undiagnosed if a diagnosis of ASD is present.…”
Section: ! "mentioning
confidence: 99%